PERSONAL MATURITY AS A COMPONENT OF PERSONAL COMPETENCE OF A SPECIAL EDUCATION TEACHER - Kovalevskaja, Ekaterina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The article is a review of research of personal competence of professionals working with children with special health opportunities. The article describes the results of the expert survey, which was conducted in order to determine personality traits that are important for professional defectologists. The correlation is established between the personal competence and personal maturity. Personal maturity is a condition for the effective and successful implementation of the activity of a special education teacher. Personal maturity is a manifestation of directedness of the personality, which has developed properties.